Leafhopper genus Nirvana Kirkaldy (Hemiptera: Cicadellidae: Evacanthinae) newly recorded from Pakistan with description of a new species - Naveed, Hassan; Zhang, Yalin (Zootaxa, 2018)
The leafhopper genus Nirvana is reported for the first time from Pakistan based on one new species described here in: Nirvana spinosa sp. nov. Habitus and genital photographic illustrations are provided for the new species.